DESKRIPSI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA BARISAN DAN DERET ARITMATIKA DI SMK - Zhopri Deswandi; Hamdani Hamdani; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research is describe the mistake of students when completing story problems arithmetic sequence and arithmetic series at senior high school. The method used in this research is descriptive method with seurvey research. The subjects in this research were students at SMK Mandiri Pontianak class XI Akuntansi II with a number of 24 students who have studied arithmetic sequences and arithmeticseries, some students were in the high category while the others were in medium category and low category. Data collection techniques used were story problems test and interviews. The results of the data analysis showed that students' mistake when completing story problems were varied,. However generally the mistake of students when completing story problems were misconceptions, errors using data, errors in interpreting language, technical errors and errors in drawing conclusions. There was no significant difference about the mistake of students when completing story problems for each student category except at mistakes in drawing conclusions, The low category students has done that mistake by a greater percentage of the others. Keywords : mistake of student, story problem